Arabic studies in the Netherlands : a short history in portraits, 1580-1950 - Vrolijk, Arnoud. (Middle East and Islamic Studies E-Books Online, Collection 2014, ISBN: 9789004262485., 2013)
Arabic is the only living language to have been taught in Dutch higher education for more than four centuries. Practical usefulness, however, has been a prerequisite from the start. Knowledge of Arabic was to promote Dutch interests in the Muslim world, or to help refute Islam. As a cognate of Classical Hebrew, the study of Arabic served as an ancillary science to Biblical studies. Nevertheless, many Arabists such as Thomas Erpenius and Jacobus Golius rose to international distinction. With more than 110 colour illustrations from the Leiden Oriental collections, Arabic Studies in the Netherlands. A Short History in Portraits, 1580-1950 by Arnoud Vrolijk and Richard van Leeuwen will help the reader to gain insight into a fascinating aspect of Dutch intellectual history.